Secondary structure analysis of the RepA mRNA leader transcript involved in control of replication of plasmid R1. - Ohman, M (1989)
The main replication control function in plasmid R1 is an antisense RNA, CopA RNA. By binding to its target (CopT) in the leader of the RepA mRNA, CopA RNA inhibits the expression of the rate-limiting RepA protein. The formation of the RNA duplex has been proposed to alter the folding around the RepA start region. Knowledge of the secondary structure of both CopA and CopT RNA is crucial for an understanding of the regulation. Previously, we reported the structure of CopA RNA under native conditions. In the present communication we have analyzed the secondary structure of the RepA leader transcript. Our main findings are: The two loops of CopA RNA have their correspondence in CopT RNA. No major structural changes are found downstream of the duplex when CopA was bound to its target RNA during transcription. Furthermore, in agreement with CopA/CopT RNA binding studies reported recently we do not find evidence for the existence of a binding window.